2020
DOI: 10.1016/j.gfs.2020.100371
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural policy reforms: Roles of markets and states in China and India

Abstract: Market reforms have been given much of the credit for China's spectacular growth performance. This paper looks at China's reform process systematically, along with India's, and argues that the Chinese state has played a key role in transforming China into a modern economic state, deploying unlimited supplies of labor and combining it with a variety of initiatives in a pragmatic, nonideological way to promote public and private investment and create productive employment in agricultural, manufacturing, and serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
(11 reference statements)
0
17
0
Order By: Relevance
“…Mukhopadhyay (2020) described India supporting its farmers with compensation for lost crops and by purchasing unsold agricultural produce. In addition to these emergency strategies to save farmers, Lele and Goswami (2020) suggested that input subsidy and investment could help. Furthermore, after the initial impact of the pandemic, farmers have been confused regarding which crops can be sold during this pandemic (Benton, 2020) and, upon returning to work, employee shortage has presented further issues, especially due to people staying home to prevent getting infected by COVID-19 (Greenville et al, 2020).…”
Section: Agriculture Post-covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Mukhopadhyay (2020) described India supporting its farmers with compensation for lost crops and by purchasing unsold agricultural produce. In addition to these emergency strategies to save farmers, Lele and Goswami (2020) suggested that input subsidy and investment could help. Furthermore, after the initial impact of the pandemic, farmers have been confused regarding which crops can be sold during this pandemic (Benton, 2020) and, upon returning to work, employee shortage has presented further issues, especially due to people staying home to prevent getting infected by COVID-19 (Greenville et al, 2020).…”
Section: Agriculture Post-covid-19mentioning
confidence: 99%
“…The government plays an important role in protecting the price and system through regulations (Lele and Goswami, 2020). Food security is closely related to trade, demand, and price (Sulser et al, 2011).…”
Section: Food Security Post-covid-19mentioning
confidence: 99%
“…From the view of sustainability of poverty alleviation policies, related policies have substantially boosted the individual net earnings of households, and the effects of poverty alleviation have continued over time [5][6][7]. Market-based reforms have reduced rural poverty [8]. Market incentives and services can improve the lives of people in poverty-stricken areas.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture is one of the main domains of public interest to ensure food security, which is basically a permanent demand driven approach. Therefore, there exist ample investment protocols, incentives, strategies and platforms due to its substantive interest and less risk factors [1]. However, the current policies in India lacks incentives for private investment in agriculture R&D of India due to austerity by government in creating a niche and transparent environment for private stakeholders to invest in agriculture R&D [2].…”
Section: Introductionmentioning
confidence: 99%
“…Commercialization of agriculture will incentivize the privatization but its spurring behavior will be facilitated with appropriate regulations, liberalization policies, trained manpower, amenable agriculture scientists with transparent protocol and fiscal policies for sharing benefits and resources (Fig. 1) [1,2]. The international donors like United States Agency for International Development (USAID), Consultative Group on International Agricultural Research (CGIAR), World Bank, National Agricultural Research Project (NARP), National Agricultural Innovation Project (NAIP) and many more have significantly contributed to agriculture R&D during Green revolution period.…”
Section: Introductionmentioning
confidence: 99%